Incidence and risk factors for emergence delirium in children undergoing surgery under general anaesthesia – A prospective, observational study - E Adithi Devi; Y V S Ravi Nagaprasad; P V Shiva; Praveen Nirmalan (Indian Journal of Anaesthesia, 2023)
Background and Aims: Emergence delirium (ED) is a common complication after general anaesthesia (GA) in children, with an incidence of 2%–80%. This study evaluated the incidence and risk factors for ED in children undergoing surgery under GA. Methods: This observational, prospective study was conducted in 336 children of either gender aged 2–13 years scheduled for surgeries under GA. Preoperative anxiety and demographics were noted. Paediatric Anaesthesia Emergence Delirium (PAED) scale, Watcha scale, and Face, Legs, Activity, Cry, Consolability (FLACC) scale were monitored 30 min postsurgery. A PAED score ≥12 and a Watcha scale score ≥3 were taken as ED. The primary outcome was the incidence of ED. An adjusted multivariate linear regression model explored the association with ED. Results: The incidence of ED was 3.87% (n = 13, 95% confidence interval [CI]: 1.80, 5.94). ED was significantly associated with male sex (β coefficient 0.06, 95% CI: 0.003, 0.11) and severe preoperative anxiety (β coefficient 0.07, 95% CI: 0.01, 0.12) in a multivariate linear regression model adjusted for other confounders. When pain scores were added to the regression model, ED was significantly associated only with pain at 0 and 10 min after surgery (P values 0.005 and 0.002, respectively). Both PAED (AUROC 0.99, 95% CI: 0.98, 1.00) and Watcha (AUROC 0.99, 95% CI: 0.98, 1.00) scores showed an excellent ability to detect ED. Conclusion: The incidence of ED was 3.87% (95% CI: 1.80, 5.94) and was significantly associated with male sex, severe preoperative anxiety and pain.